The progressive era's health reform movement : a historical dictionary - Engs, Ruth Clifford (Praeger, 2003)
Religious, political, social, and health reform earmarked the Progressive Era. The era's health reform movement--like today's clean living movement--saw campaigns against alcohol, tobacco, drugs, and sexuality. It included crusades for exercise, vegetarian diets, and alternative health care and concerns about eugenics and new diseases. Covering the years leading up to the Progressive Era through the 1920s, this book provides entries on the central figures, events, crusades, legislation, publications and terms of the health reform movements, while a detailed timeline ties health reform to politic.